Local Community Perceptions of the Presence of Paucidentomys vermidax in Buffer Villages of Gandang Dewata National Park, West Sulawesi - Demmaraya, Jhon; Nurdin, Muhammad Rizaldi Trias Jaya Putra; Hakim, Sufyan; Pati, Maipa Dia (Center for Ecology, Conservation and Ethnobiology Studies, Universitas Sulawesi Barat, 2025)
This study aimed to examine the presence of Paucidentomys vermidax and community perceptions in five buffer villages surrounding Gandang Dewata National Park. The research employed a quantitative approach using a survey method. Respondents were selected through cluster sampling, involving 66 individuals from various professions who have direct interaction with river ecosystems, including hunters, farmers, and local residents who frequently carry out activities around river areas. Data were collected through questionnaire-based interviews to obtain information on the frequency of species sightings and its utilization by the local community. The results showed that 60.61% of respondents had seen Paucidentomys vermidax, while 51.5% stated that the species is used as a food source by local communities. The level of community knowledge about this species is influenced by their proximity to its natural habitat and by activities closely related to river environments, such as farming and hunting. These findings indicate that the presence of P. vermidax is still recognized by communities living in the buffer areas of Gandang Dewata National Park and reflects the relationship between local communities and endemic fauna diversity in the region. This study provides preliminary information on the presence of Paucidentomys vermidax in the buffer zones of Gandang Dewata National Park and highlights the importance of considering local knowledge and community perceptions in conservation efforts for endemic species in Sulawesi